2010
DOI: 10.2139/ssrn.1721801
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hazardous Waste and Contaminated Land

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 94 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…There is a large and related literature on the economics of waste management more generally, but this review does not focus on this extensive literature, as it is worthy of a complete review on its own; some of this area is covered in Sigman & Stafford (2011). However, it is worth briefly mentioning some of these important papers for the reader who may be interested in international waste trade issues within the context of waste management more generally.…”
Section: International Waste Trade and Related Waste Management Litermentioning
confidence: 99%
“…There is a large and related literature on the economics of waste management more generally, but this review does not focus on this extensive literature, as it is worthy of a complete review on its own; some of this area is covered in Sigman & Stafford (2011). However, it is worth briefly mentioning some of these important papers for the reader who may be interested in international waste trade issues within the context of waste management more generally.…”
Section: International Waste Trade and Related Waste Management Litermentioning
confidence: 99%
“…They indicated that the speeding up effect of funding was small compared with the amount of funding needed, although funding could accelerate the remediation process in two of the four different states. Sigman and Stafford (2010) reviewed the socioeconomic literature on regulation of hazardous waste and cleanup of contaminated sites, focusing on empirical analysis. Relatively more existing studies have examined property values before and after cleanup using stated preference approaches and hedonic price techniques (e.g., Alberini et al 2005;McCluskey and Rausser 2003;Greenstone and Gallagher 2008;US Environmental Protection Agency 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result indicates that full removal raises the cleanup costs by approximately 236 % and partial removal does so by approximately 180 %. As Sigman and Stafford (2010) noted, removal actions are more expensive than remedial actions. Significant effects for toxicity are similar to the results by Barth and McNichols (1994) that indicated significant effects of hazard score by the EPA and pollution of groundwater.…”
Section: Costs and Periodsmentioning
confidence: 99%
See 2 more Smart Citations